An interdisciplinary approach to the assessment of water recycling technology options. (29th August 2007) - Jeffrey, Paul; Seaton, Roger A.F.; Parsons, Simon A.; Judd, Simon J.; Stephenson, Tom
Whilst work on the development of engineering options for water recycling has continued apace over the last decade, less attention has been paid to the problem of selecting appropriate technologies for particular applications. This paper firstly reviews the motivations for a cross-disciplinary approach to technology selection in this context, highlighting the process of translating research findings into practical and socially acceptable opportunities. It goes on to report early experience from an interdisciplinary collaboration which seeks to assess the suitability of specific water recycling options for urban environments. Conclusions relate primarily to the effective application of interdisciplinary research programmes to water management issues.